Penerapan model pembelajaran role playing berbantuan cerita rakyat untuk meningkatkan keterampilan berbicara bahasa Jawa krama peserta didik kelas v sekolah dasar - Maulida Uswatun Hasanah; Joko Daryanto (Didaktika Dwija Indria, 2025)
This study aims to improve the Javanese krama speaking skills of fifth-grade students through the application of role-playing learning models assisted by folk tales. The method used in this study is a Qualitative Classroom Action Research (CAR) type which is implemented in three cycles, each cycle consisting of two meetings. The subjects in this study were 16 students and 1 fifth-grade teacher of Kedawung 4 Public Elementary School. Data collection techniques in this Classroom Action Research (CAR) include observation, interviews, and performance. The results of the study show that the percentage of the application of the role-playing learning model in cycle I was 64.53%, cycle II was 78.8% and cycle III was 90.57%. The results of the performance of Javanese krama speaking skills in cycle I were 70.31%, cycle II was 77.81% and cycle III was 82.18%. Based on the results obtained, students' Javanese krama speaking skills were proven to increase rapidly. So it can be concluded that the Javanese krama language speaking skills of grade V students increased due to the influence of the application of the role playing learning model assisted by folk stories.